2013
DOI: 10.1093/bja/aet057
|View full text |Cite
|
Sign up to set email alerts
|

Role of glycogen synthase kinase-3β in ketamine-induced developmental neuroapoptosis in rats

Abstract: Ketamine-induced neuroapoptosis is associated with a temporal decrease in GSK-3β phosphorylation, and simultaneous administration of lithium mitigated this response. These findings suggest that GSK-3β is activated during this ketamine-induced neuroapoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Recently, it has been reported that activation of PI3K/Akt/GSK-3β signaling had a protective effect on ketamine-induced neuroapoptosis [21,[43][44][45]. Moreover, Liu et al reported that lithium, an inhibitor of GSK-3β, could attenuate ketamine-induced neuroapoptosis [46]. Interestingly, lithium carbonate is an important therapeutic drug for psychosis while abuse of ketamine may induce psychosis [47].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that activation of PI3K/Akt/GSK-3β signaling had a protective effect on ketamine-induced neuroapoptosis [21,[43][44][45]. Moreover, Liu et al reported that lithium, an inhibitor of GSK-3β, could attenuate ketamine-induced neuroapoptosis [46]. Interestingly, lithium carbonate is an important therapeutic drug for psychosis while abuse of ketamine may induce psychosis [47].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the mechanism underlying astrocytes-induced paracrine effect can help develop potential therapeutic strategies to avoid propofol-induced neurotoxicity. PI3K/Akt and glycogen synthase kinase (GSK3β) have been shown to be involved in various cell survival pathways including developing human embryonic stem cell-derived neurons 23,24,53 . Blockage of Akt, a negative regulator of GSK3β or activation of GSK3β caused cells to undergo the apoptotic process 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…This toxic effect was associated with the decrease in Akt and GSK3β phosphorylation (p-GSK3β) and co-administration of lithium with ketamine attenuated the neuronal death through deactivation of GSK3β. 53 Recently, evidence linking propofol-induced neurotoxicity and defective STAT3/SPOUT2/Akt pathway was reported in human neurons 23 . Despite convincing evidence of involvement of Akt/ GSK3β pathway in developing neuronal death, whether astrocyte-derived BDNF regulates this pathway to increase neuronal survival in propofol-injured neurons is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The Akt pathways are important intracellular signaling systems that act downstream of the neurotrophin receptors (Mullen et al, 2012). Previous studies indicated that ketamine induces neuroapoptosis by blocking the NMDA receptor activity and decreasing the pAkt levels (Shang et al, 2007;Straiko et al, 2009;Liu et al, 2013b;Li et al, 2013) and that the Akt pathway prevents ketamineinduced neuroapoptosis (Shang et al, 2007;Liu et al, 2013b;Li et al, 2013). Moreover, the NMDAR antagonist MK-801 triggers neuroapoptosis in the neonatal cortex by depressing BDNFAkt signaling (Dzietko et al, 2004).…”
Section: Discussionmentioning
confidence: 99%